2018
DOI: 10.1086/698467
|View full text |Cite
|
Sign up to set email alerts
|

Sequences of Circadian Clock Proteins in the Nudibranch Molluscs Hermissenda crassicornis, Melibe leonina, and Tritonia diomedea

Abstract: While much is known about the genes and proteins that make up the circadian clocks in vertebrates and several arthropod species, much less is known about the clock genes in many other invertebrates, including nudibranchs. The goal of this project was to identify the RNA and protein products of putative clock genes in the central nervous system of three nudibranchs, Hermissenda crassicornis, Melibe leonina, and Tritonia diomedea. Using previously published transcriptomes (Hermissenda and Tritonia) and a new tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 77 publications
1
12
0
Order By: Relevance
“…In the Mus genus bmal , a homolog of cycle , binds to clock and regulates the transcription of period and npcry (Shearman et al, 2000). Although not included in this study, Cook et al , (in press) have demonstrated the presence of bmal in the M. leonina transcriptome. Therefore, the molecular mechanisms involved in the M. leonina circadian clock(s) contains the same genes present in the mammalian system and the connection/pathway of these genes is also similar.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the Mus genus bmal , a homolog of cycle , binds to clock and regulates the transcription of period and npcry (Shearman et al, 2000). Although not included in this study, Cook et al , (in press) have demonstrated the presence of bmal in the M. leonina transcriptome. Therefore, the molecular mechanisms involved in the M. leonina circadian clock(s) contains the same genes present in the mammalian system and the connection/pathway of these genes is also similar.…”
Section: Discussionmentioning
confidence: 98%
“…Sequence-specific RNA probes were developed by Biosearch Technologies for clock , period , and photoreceptive and non-photoreceptive cryptochrome (pcry and npcry , respectively), based on sequences derived from RNA transcriptomes (Cook et al , in press). In brief, 48 non-overlapping, 20-nucleotide RNA probes were designed for each transcript, with each probe being conjugated to a fluorophore.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tamvacakis et al identified genes related to learning and memory in the CNS transcriptome of Hermissenda crassicornis . 40 Cook et al 41 fingered sequences of circadian clock proteins Hermissenda crassicornis , Melibe leonina , and Tritonia diomedea . Such results enable identification of genes encoding cyclic nucleotide-gated channels, proton channels, NOS, components of the cyclic AMP and cGMP cascades, a diversity of putative 5HT receptors and many neuropeptides.…”
Section: Modeling and Measuring Camp Actionsmentioning
confidence: 99%
“…Molecular data on rhythms and clocks in marine invertebrates have become increasingly available over the last decade, now including the bivalves Mytilus californianus (Connor and Gracey, 2011) and Crassostrea gigas (Perrigault and Tran, 2017), the sea slugs Hermissenda crassicornis , Melibe leonina , and Tritonia diomedea (Cook et al, 2018; Duback et al, 2018), the isopod Eurydice pulchra (Wilcockson et al, 2011; Zhang et al, 2013; O’Neill et al, 2015), the amphipod Talitrus saltator (Hoelters et al, 2016), the lobsters Nephrops norvegicus (Sbragaglia et al, 2015) and Homarus americanus (Christie et al, 2018), the mangrove cricket Apteronemobius asahinai (Takekata et al, 2012), the copepods Calanus finmarchicus (Häfker et al, 2017), and Tigriopus californicus (Nesbit and Christie, 2014), the Antarctic krill Euphausia superba (Mazzotta et al, 2010; Teschke et al, 2011; Pittà et al, 2013; Biscontin et al, 2017), the Northern krill Meganyctiphanes norvegica (Christie et al, 2018), the marine midge C. marinus (Kaiser and Heckel, 2012; Kaiser et al, 2016), and the marine polychaete P. dumerilii (Zantke et al, 2013; Schenk et al, 2019). On the marine vertebrate side, especially teleost fish species have been investigated (Park et al, 2007; Sánchez et al, 2010; Hur et al, 2011; Watanabe et al, 2012; Vera et al, 2013; Rhee et al, 2014; Toda et al, 2014; Mogi et al, 2015; Okano et al, 2017).…”
Section: Introductionmentioning
confidence: 99%